(untitled) (Nepal Journal of Environmental Science, 2025)
Wetlands, especially lakes, are highly dynamic ecosystems with diverse ecological roles and significant economic benefits, including water purification, groundwater replenishment, nutrient retention and biodiversity conservation. This study assessed the hydrochemical characteristics, vegetation status and seasonal dynamics of three key wetlands: Ghodaghodi, Jokhar and Rani Lake, located in the lowland region of Sudurpashchim Province, Nepal. Hydrochemical analysis revealed that all measured parameters remained within WHO and National Drinking Water Quality Standards (NDWQS) guidelines; however, anthropogenic impacts, particularly in Jokhar Lake, led to elevated nitrate concentrations and reduced dissolved oxygen levels. Seasonal patterns showed increased temperature, electrical conductivity (EC), total dissolved solids (TDS), and nutrient concentrations during summer, likely due to runoff and increased human activities. The Water Quality Index (WQI) ranged from excellent in Rani Lake (WQI = 23.40-30.01) to moderately polluted in Jokhar Lake (WQI = 61.45-71.52), whereas Ghodaghodi showed excellent to moderately polluted status (WQI=41.01-51.12). Vegetation assessments revealed the highest species richness and diversity indices in Ghodaghodi Lake, followed by Jokhar and Rani lakes, with higher diversity attributed to complex landscapes and botanical garden proximity. Rani Lake, despite lower species diversity, maintained better water quality due to strict protection measures and minimal human interference. The study revealed significant seasonal variations in the water quality of all the study lakes. Ghodaghodi showed a reduced open water area and increased pollution in summer, Jokhar had high shoreline loss with moderate pollution year-round, while Rani remained stable with good water quality. Thus, the results underscore the importance of effective targeted conservation strategies to manage and preserve these unique wetland ecosystems. Additionally, this research also highlights the critical role of understanding and conserving wetlands under different management regimes in biodiversity conservation, water quality regulation under the context of global climate change.